Revealing the biosynthesis of guanitoxin, a naturally occurring neurotoxic organophosphate - Camargo, Stella de Lima (2020)
Sphaerospermopsis torques-reginae is a planktonic freshwater cyanobacteria species with broad distribution in several Brazilian aquatic environments. Some strains of this species are known to produce the neurotoxic organophosphate guanitoxin (GNT) as well as spumigin and anabaenopeptin, both protease inhibitors. GNT is a powerful irreversible inhibitor of the acetylcholinesterase enzyme which acts in the peripheral nervous cells of mammals. While GNT has been known for decades, the genes encoding its biosynthetic pathway are unknown. The sequencing and assembly of the S. torques-reginae ITEP-024 5.2 Mbp genome allowed us to identify a 12.5 kbp gene cluster potentially involved in GNT production. To rigorously validate our genomic finding, we over-expressed, purified and characterized many of the GNT biosynthetic enzymes in vitro, confirming our proposed biosynthetic cluster. Also, a vector was designed that assembled two of the biosynthetic genes with the goal to produce the intermediate enduracididine, a rare amino acid. The combination of in vivo and in vitro experiments successfully validated our proposed gene cluster. Using our results, we showed that this biosynthetic gene cluster was actively expressed in one of the largest cyanobacterial blooms hotspots, Lake Erie, Toledo, USA. This suggest that the potent neurotoxin guanitoxin could be in drinking water supplies around the world. Worryingly, guanitoxin is often overlooked and rarely tested for in reservoirs in spite of the danger it poses. This study contributed to the characterization of the GNT biosynthetic pathway, which may generate a patent enabling the development of rapid and sensitive methods for the detection and monitoring of this toxin in freshwaters used for public supply. Moreover, this work may offer potential for the development of new neurological medicines and tools